HCI in Business, Government and Organizations: 7th International Conference, HCIBGO 2020, Copenhagen, Denmark, July 19-24: Proceedings - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2020)
This volume LNCS 12204 constitutes the refereed proceedings of the 7th International Conference on Business, Government, and Organizations, HCIBGO 2020, which was held in July 2020 as part of HCI International 2020 in Copenhagen, Denmark. 1439 papers and 238 posters were accepted for publication after a careful reviewing process. The 42 papers presented in this volume are organized in topical sections named: digital transformation and intelligent data analysis and social media, digital commerce and marketing.